AE-SiGMA ANALYSIS IN SPLIT-TENSILE TEST OF FIBER-REINFORCED CONCRETE (FRC) AT MESO-SCALE - Mondoringin, Mielke R.I.A.J.; Ohtsu, Masayasu (JURNAL ILMIAH MEDIA ENGINEERING, 2015)
Crack control plays a crusial role in the performance life of concrete structures. It present a serious treat to the performanceÂ  of concrete structures. Micro-cracking will appear when the strength of concrete is approached. Each of micro-crack occured inside concrete will produce a transient elastic wave which could be used to detect and localize cracks as well as to analize kinematically the fracture mechanisms in concrete. In this scientific paper, the SiGMA analysis is applied to the split-tensile tests of FRC to study the relation between the generation of macro-scale tensile crack and accumulation of meso-scale cracks as well as to know the role of the applied fiber on the cracking process of concrete. Results showed that the relation between macro-scale tensile failure and nucleation of AE sources in meso-scale is clarified in Split-tensile test. At the macro-scale, tensile-type cracks are only observed, while all kinds of tensile, mixed-mode and shear cracks are identified at the meso-scale. During propagation of tensile cracks at the macro-scale, other types of AE sources of mixed-mode and shear cracks were actively identified. Thus, nucleation of the fracture process zone is confirmed around the final failure surface.Mechanisms of macro-scale tensile failure process in concrete are clarified as the crack accumulation process at meso-scale determined by the SiGMA analysis. There exists a clear relation between macro-scale tensile failure process and nucleation of AE- sources in the meso-scale in the split-tensile test for the tensile strength of concrete. KEYWORDS:AE-SiGMA, fracture, Split-tensile-test, tensile-cracks,FRC,AE hits, AE events